Penyiraman Tanaman Otomatis pada Tanaman Cabai Rawit dengan Metode Simple Additive Weighting - Nisa'ul Nurfajri Arofah; Fikra Titan Syifa; Indah Permatasari (Universitas Sarjanawiyata Tamansiswa, 2023)
Conventional watering of plants requires more time and effort to do so. Often plant owners forget to water the plants which can cause the plants to die. Sometimes the amount of water that is sprinkled does not match the water needed by the plants. From these problems, the author will create an IoT-based automatic plant watering system using the SAW (Simple Additive Weighting) method. In this study the authors used capsicum frutescens, Node MCUESP8266 as a microcontroller, soil moisture capacitive as a soil moisture sensor, and DHT11 as a temperature sensor. The results showed that the system can water the plants automatically with a capacitive soil moisture sensor reading accuracy of 96.63% and a DHT11 sensor reading of 98.98%. Besides that, based on the application of the SAW method in making decisions for plants that have the most right to be watered, namely conditions that have a final result of more than or equal to 36.